Nitrate reductases and hemoglobins control nitrogen-fixing symbiosis by regulating nitric oxide accumulation. (2nd September 2020) - Berger, Antoine; Boscari, Alexandre; Puppo, Alain; Brouquisse, Renaud
Abstract: The interaction between legumes and rhizobia leads to the establishment of a symbiotic relationship between plant and bacteria. This is characterized by the formation of a new organ, the nodule, which facilitates the fixation of atmospheric nitrogen (N2 ) by nitrogenase through the creation of a hypoxic environment. Nitric oxide (NO) accumulates at each stage of the symbiotic process. NO is involved in defense responses, nodule organogenesis and development, nitrogen fixation metabolism, and senescence induction. During symbiosis, either successively or simultaneously, NO regulates gene expression, modulates enzyme activities, and acts as a metabolic intermediate in energy regeneration processes via phytoglobin-NO respiration and the bacterial denitrification pathway. Due to the transition from normoxia to hypoxia during nodule formation, and the progressive presence of the bacterial partner in the growing nodules, NO production and degradation pathways change during the symbiotic process. This review analyzes the different source and degradation pathways of NO, and highlights the role of nitrate reductases and hemoproteins of both the plant and bacterial partners in the control of NO accumulation. Abstract : Nitrate reductases and hemoproteins (phytoglobins and Hmp) are key regulatory elements of nitric oxide (NO) control during nitrogen-fixing symbiosis. Both plant and bacterial partners are involved in NO regulation.